Improving Students’ Report Text Writing through Project-Based Learning with Padlet (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This Classroom Action Research aims to improve students’ ability in writing report texts by implementing Project-Based Learning (PjBL) integrated with Padlet in a tenth-grade English class. The problem identified was students’ limited ability to organize and express ideas in report texts. In line with Kurikulum Merdeka’s emphasis on student-centered learning and the development of Profil Pelajar Pancasila, the researcher designed a contextual learning activity where students explored and wrote about traditional dances using Padlet as a collaborative platform. Conducted over two cycles, data were gathered from students’ written products, observations, and reflection journals. Results showed significant improvement in students’ writing structure, vocabulary, and engagement. The study concludes that PjBL supported by Padlet is an effective approach to enhance writing competence, foster digital literacy, and align with the principles of Kurikulum Merdeka.